医療訴訟の概要 - 德増, 誠一 (日本口腔外科学会雑誌, 2024)
1 . A Basic Framework of a Medical Malpractice Lawsuit; Section 2 of the text 　Customary, Article 709, 715 of the Civil Code, in regards to tort, or Article 415 of the Civil Code, in regards to default, is selected as a legal bases for a claim for damages in a Medical Malpractice Lawsuit. 　Allegation propositions in a Medical Malpractice Lawsuit are thought of as Negligence, Infringement of Rights or Interests, Damage, and Causation. 　Negligence is judged on the basis of the Medical Standards, on the premise of the facts which Doctors were able to know at the time of the medical treatment; Negligence is structured as being judged prospectively. 　In contrast, Causation is judged on the basis of reasonable inference, from presumptions of various facts, on the premise of all information which became evident at the time of trial after the time of the medical treatment; Causation is structured as being judged retrospectively. 　 2 . Specific Examples of Considerations in Judgments; Section 3 of the text 　Specific Examples of Considerations in Judgments are as described in Section 3 of the text